2009
DOI: 10.2319/110408-563r.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intrusive Force on Selected Determinants of Pulp Vitality

Abstract: Objective: To determine the activity of aspartate aminotransferase (AST) in the pulp of orthodontically intruded teeth and to test the sensitivity of these teeth by means of electrical pulp testing (EPT). Materials and Methods:The study sample consisted of 21 healthy subjects who needed extraction of first premolars for orthodontic reasons. In every subject, one premolar included in a 0.016Љ-0.022Љ stainless steel spring from the first molar and loaded by the force was regarded as a test tooth. The magnitude o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 27 publications
2
24
2
Order By: Relevance
“…Another reason that no clear effects on pulpal tissues have been found in the present study might be that our appliance induced an almost bodily movement of the molar block (Ren et al, 2004;Ren et al, 2003), while others used tipping movements of the first molar only (Abi-Ramia et al 2010;Bletsa et al 2006;Grunheid et al 2007;Santamaria et al 2007;Shigehara et al 2006;Tripuwabhrut et al 2010), intrusion (Barwick & Ramsay 1996;Ikawa et al 2001;Konno et al 2007;Raiden et al 1998;Ramazanzadeh et al 2009;Stenvik 1971;Veberiene et al 2009), or extrusion (Ramazanzadeh et al 2009;Stenvik 1971;Subay et al 2001).…”
Section: Discussioncontrasting
confidence: 55%
“…Another reason that no clear effects on pulpal tissues have been found in the present study might be that our appliance induced an almost bodily movement of the molar block (Ren et al, 2004;Ren et al, 2003), while others used tipping movements of the first molar only (Abi-Ramia et al 2010;Bletsa et al 2006;Grunheid et al 2007;Santamaria et al 2007;Shigehara et al 2006;Tripuwabhrut et al 2010), intrusion (Barwick & Ramsay 1996;Ikawa et al 2001;Konno et al 2007;Raiden et al 1998;Ramazanzadeh et al 2009;Stenvik 1971;Veberiene et al 2009), or extrusion (Ramazanzadeh et al 2009;Stenvik 1971;Subay et al 2001).…”
Section: Discussioncontrasting
confidence: 55%
“…It has been reported that orthodontic tooth movements like intrusion might also influence PST response [7, 40]. Radiographic examination, albeit limited to two-dimensional plain film radiographs, did not reveal any close proximity between the OMIs and the roots of the teeth.…”
Section: Discussionmentioning
confidence: 89%
“…It is known that orthodontic tooth movement can affect PST response temporarily [6], but sensibility is thought to return to normal after completion of treatment. The authors state that there is no agreement in the literature regarding potential long-term sequelae: reported pulpal responses after orthodontics included circulatory vascular stasis and necrosis [7]. Cases of pulpal necrosis following orthodontic therapy have been occasionally reported [8, 9], but this is unusual.…”
Section: Introductionmentioning
confidence: 99%
“… 13 Increased AST activity has been reported in the dental pulp, and in the GCF in cases of orthodontic treatment. 4 14 15 16 17 18 These results indicate that AST present in the dental pulp tissue might have a role in the early events leading to inflammatory changes. Most studies on the effects of orthodontic treatment on pulp have been relatively limited in duration, ranging from 20 seconds (sec) to 152 days.…”
Section: Introductionmentioning
confidence: 84%